PSYCHOLOGICAL WELL-BEING MAHASISWA YANG MENGIKUTI PEMBELAJARAN DARING PADA MASA PANDEMI COVID-19 - Adinda Yusvika Rahmawati; Wakhid Musthofa (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Tarumanagara, 2021)
The purpose of this study is to describe the Psychological well-being of students participating in online learning during the COVID-19 pandemic. This research was conducted at the Islamic Psychology Study Program, IAIN Surakarta. This type of research is qualitative phenomenology. There are 3 informants selected by purposive sampling. Data collection techniques through structured interviews. Credibility of data using source triangulation. The data analysis technique used interpretative phenomenological analysis (IPA). There are three main themes found in the study, namely 1) Self-acceptance, 2) Perceived impact, 3) Expectations. The results of this study indicate that students have psychological well-being which is influenced by each dimension. The implications of this study are more interesting after the self-acceptance dimension is achieved, it is easier to achieve other dimensions, namely, life goals, environmental mastery, autonomy, positive relationships with others, and personal growth. Individuals who have gratitude will show positive emotions, gratitude has a relationship with happiness, so that the three informants have a mindset to continue to be grateful in whatever happens, therefore the informants are individuals who feel happiness. Keywords : Online learning, Psychological well-being, Gratitude